ROLE OF SELECTION INDICES IN ASCERTAINING HIGH YIELDING DROUGHT STRESS TOLERANT CHICKPEA (CICERARIETINUM L.) - H. Khan; R. Gul; N. U. Khan; R. Naz; S. Shah; N. Asim; A. Latif (Journal of Animal and Plant Sciences, 2018)
Drought is one of the major causes of limited crop production. The present study investigated the influence of drought stress on seed yield characteristics in twenty (10 Desi and 10 Kabuli) chickpea genotypes. RCB design with three replicates was used to carry out a field experiment with two humidity regimes (stressed and non-stressed). Significant differences were observed among genotypes for potential yield (YP) and stressed yield (YS) as well as for eight selection indices. There was significant and positive correlation of potential yield (YP) and stressed yield (YS) with MP, HM, GMP, and STI under both the environments, whilst yield showed significant negative correlation with TOL under rainfed condition and significant positive correlation with TOL under irrigated condition. The STI, K1STI, MP, GMP and PI indices exhibited strong correlation with YP, while YI showed strong correlation with YS; therefore, YS can discriminate drought tolerant genotypes with high grain yield under stress conditions. Genotype NKC-5-S-20 and NKC-5-S-17 showed highest TOL, STI and lowest YTI, Moreover they revealed greater yield under non-stress and stress conditions. So, these genotypes could be suggested for release as cultivars after multi location tests. The studied germplasm is highly variable and could be efficiently used in future chickpea breeding programs.
Keywords: chick pea; correlation coefficient; drought; polygenic; selection index